Impact of the World Health Organization Surgical Safety Checklist on Patient Safety. (August 2019) - Haugen, Arvid S.; Sevdalis, Nick; Søfteland, Eirik
Abstract : The incidence of surgical complications has remained largely unchanged over the past two decades. Inherent complexity in surgery, new technology possibilities, increasing age and comorbidity in patients may contribute to this. Surgical safety checklists may be used as some of the tools to prevent such complications. Use of checklists may reduce critical workload by eliminating issues that are already controlled for. The global introduction of the World Health Organization Surgical Safety Checklist aimed to improve safety in both anesthesia and surgery and to reduce complications and mortality by better teamwork, communication, and consistency of care. This review describes a literature synthesis on advantages and disadvantages in use of surgical safety checklists emphasizing checklist development, implementation, and possible clinical effects and using a theoretical framework for quality of provided healthcare (structure—process—outcome) to understand the checklists' possible impact on patient safety. Abstract : Surgical safety checklists are reported to reduce complications and mortality. Checklists should address critical and basic routines in anesthesia and surgery, so clinicians may focus on solving critical problems.